Consecutive chemical trees with respect to energy of graph. (3rd April 2021) - Kazi, Sabeena
Abstract: A chemical tree is a tree in which no vertex has a degree greater than four. Two trees T 1 and T 2 of same orders p, are said to be consecutive trees with respect to the energy, if there exists no tree T of order p satisfying E ( T 1 ) < E ( T ) < E ( T 2 ). In this paper the author gives the consecutive chemical trees with respect to energies with edge independence number, denoted by t p ( i ) where i is the edge independence number and i = 2, 3 and p is the number of vertices. And give the table listing all the possible energy consecutive chemical trees tp ( i ), i = 2, 3, their polynomials and energies.